PENGEMBANGNAN POTENSI PERKEBUNAN SEBAGAI KOMODITAS UNGGULAN DI DESA PROBUR UTARA KECAMATAN ALOR BARAT DAYA - Jefri Moban; Vebrianus Petrus Barai; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This research aims to examines the potential of candlenut (Aleurites moluccanus) cultivation as a leading commodity in Probur Utara Village, Alor Barat Daya District. Candlenut is the dominant plantation crop, covering 1–5 hectares, and has long served as a source of income for local residents. This study uses a qualitative descriptive approach based on interviews with village authorities. The results indicate that candlenut has strong prospects for development due to land suitability, community knowledge, and stable market demand. However, its development is constrained by limited capital, lack of postharvest innovation, weak marketing access, and insufficient supporting facilities. Integrated development strategies—such as training, value-added processing, farmer group strengthening, and supply chain development—are required to enhance candlenut’s competitiveness as a leading commodity.